Profiling the Genome-Wide Landscape of Short Tandem Repeats by Long-Read Sequencing - Liu, Zhenhua; Zhao, Guihu; Xiao, Yuhui; Zeng, Sheng; Yuan, Yanchun; Zhou, Xun; Fang, Zhenghuan; He, Runcheng; Li, Bin; Zhao, Yuwen; Pan, Hongxu; Wang, Yige; et al. (Frontiers in Genetics, 2022)
Background: Short tandem repeats (STRs) are highly variable elements that play a pivotal role in multiple genetic diseases and regulation of gene expression. Long reads sequencing (LRS) offers a potential solution to genome-wide STR analysis. However, characterizing STRs in human genomes using LRS on a large population scale has not been reported. Methods: We conducted the large LRS-based STR analysis in 193 unrelated samples of Chinese population and performed genome-wide profiling of STR variation in human genome. The repeat dynamic index (RDI) was introduced to evaluate the variability of STR. We sourced the expression data from the Genotype-Tissue Expression to explore the tissue specificity of highly variable STRs related genes across tissues. Enrichment analysis were also conducted to identify potential functional roles of the high variable STRs. Results: This study reports the large-scale analysis of human STR variation by LRS, and offers a reference STR database based on LRS dataset. We found the disease associated STRs (dSTRs) and STRs associated with expression of nearby genes (eSTRs) were highly variable in the general population. Moreover, tissue-specific expression analysis showed those highly variable STRs related genes presented highest expression level in brain tissues, and enrichment pathways analysis found those STRs are involved in synaptic function related pathways. Conclusion: Our study profiled the genome-wide landscape of STR using LRS and highlighted the highly variable STRs in human genome which provide a valuable resource for studying the role of STRs in human disease and complex traits.